Sexuality as a tool to gain political power: an introspection of Zimbabwean elections of 2013 - Moyo, Talent (Routledge, 2021)
The paper examines how the discourse of sexuality was employed to gain political legitimacy by the Zimbabwe African National Union-Patriotic Front (ZANU-PF) to out-manoeuvre their political rivals Movement for Democratic Change-Tsvangirai Faction (MDC-T) in the Zimbabwean elections of 2013. In the context of Zimbabwe politics, the nexus between sexual discourse and political contests presents a conspicuous shift from dominant day-to-day mundane political debates centred on policy to debates of personal (mis)conduct and morality. The nexus between sexuality and political legitimacy is analysed using Michel Foucault’s ideas on sexuality: repressive hypothesis and biopower. The paper maintains that the media have been used to disseminate the discourse of sexuality to the electorate. Importantly, the influence of media is scrutinised using the theory of mass communication and media politics as articulated by Castells, and the Propaganda Model postulated by Herman and Chomsky. Through Critical Discourse Analysis and results from unstructured interviews the paper observes that the discourse of sexuality had a considerable bearing on gaining political power. Lastly, the paper observes that, although the discourse of sexuality has a symbiotic relationship with amassing political power, there were other factors that influenced the electoral outcome.